The fears in our life: Những nỗi sợ trong cuộc sống - Võ, Xuân Quang (Khoa Học Công Giáo và Đời Sống, 2022)
To the human eye, this world is very beautiful, but it is also insecure and full of disasters, wars, and diseases. As a consequence, we are living with fears. This writing investigates three kinds of fears and how we can overcome each fear. To answer the research question, I base the writing on the teaching of the Gospel and the Catholic doctrine. In the end, the writing shows that we can overcome our fears if we put our life in God’s hands and keep His commandments. I suggest you use this writing to reflect and strengthen your faith in God.